Profil Fleksibilitas Atlet Beladiri PPLM - Dwi Indra Kurniawan; Iwan Setiawan; Slamet Sukriadi (Jurnal Muara Olahraga, 2026)
Flexibility is an essential component of physical fitness that plays a crucial role in supporting performance and preventing injuries in martial arts athletes. This study aimed to determine the flexibility profile of martial arts athletes at the Student Training and Education Center (PPLM) Jakarta. This research employed a quantitative descriptive method with a survey approach. The subjects consisted of 20 martial arts athletes from taekwondo, pencak silat, and karate. The instruments used were the Sit and Reach Test to measure lower body flexibility and the Shoulder Flexibility Test (Back Scratch Test) to assess right and left shoulder flexibility. Data were analyzed using descriptive statistics. The results showed that the average lower body flexibility was 23.4 cm, categorized as moderate. Meanwhile, upper body flexibility showed average values of 3.1 cm for the right shoulder and 2.8 cm for the left shoulder, both categorized as high. In conclusion, the flexibility profile of PPLM Jakarta martial arts athletes is generally good, with upper body flexibility being more dominant than lower body flexibility. These findings indicate the need for a more balanced flexibility training program to optimize performance and reduce injury risk.